A Model Comparison Study of Fragment Production in 140 A MeV 58, 64Ni+9Be Reactions*Supported by the Program for Science and Technology Innovation Talents in Universities of Henan Province under Grant No 13HASTIT046. (July 2015) - Ma, Chun-Wang; Zhang, Yan-Li; Wang, Shan-Shan; Qiao, Chun-Yuan
<x content-type="archive" xml:space="preserve">Abstract</x> The cross sections of fragments produced in the 140 A MeV58, 64Ni+9 Be projectile fragmentation reactions are calculated by using the antisymmetrized molecular dynamics (AMD) model, the modified statistical abrasion-ablation (SAA) model, and the empirical EPAX2/EPAX3 formulae. The Gogny-g0 interaction is taken as the effective nucleon-nucleon interaction in the AMD calculation, and the decays of fragments obtained from the AMD results are calculated by using the GEMINI code. The calculated cross sections of fragments are compared.